Meme Work in Anti-Veg*nism Humor on Instagram: Reflections on Hate Speech and Social Media Regulation - Costa, Thiago (AoIR Selected Papers of Internet Research, 2026)
This paper explores how anti-veg*nism humor memes on Instagram fuel hate speech and reinforce hegemonic masculinities. A critical visual analysis (Rose, 2016) of 28 memes from the profile @lagrimasdevegano (veganstears) reveals that disparagement humor (Ford, 2015) disguises prejudice as jokes, promoting intolerance and gender stereotypes. These memes link veganism to fragility and femininity, reinforcing conservative ideologies that glorify meat consumption as a marker of masculinity. The study underscores the difficulties digital platforms face in regulating such content, given humor’s ambiguity and a maximalist interpretation of free speech. It advocates for culturally sensitive moderation and media education to create a more inclusive digital space.